A comparison of the syntax of newspaper editorials / Muhammad Nasiruddin Aziz - Aziz, Muhammad Nasiruddin (2020)
Research has shown that Malaysian students at all levels and graduates seeking jobs experience difficulties in expressing their ideas in English. To address these difficulties, Malaysian users of English could obtain insights into sentence patterns used in easily-accessed and well-written articles like editorials. This study examines the syntax of newspaper editorials published in different contexts in which English is used, guided by two research questions. The first seeks answers to ways in which main sentences are structured in editorials published in English used in first and second language contexts, while the second explores differences in the structures of sentences in these editorials. This exploratory research examined a total of 100 clauses from four editorials: The Star, The Straits Times, The Sun, and The Wall Street Journal and the sentences were analysed using Morenberg’s syntactic model. The results of the cross-tabulation and C-Square analysis found that the sentences employed a wide range of syntactic patterns comprising dissimilar arrangements comprising both obligatory and optional elements but many syntactic features were consistent. These findings suggest that users of English could study the syntax of editorials written by proficient writers to improve their communication skills, and they have implications for the teaching of writing and professional communication.